The effect of several agricultural applications on the weight of broad-leaved weeds and the yield of alfalfa feed - Mahdi Al-Badr; Shaker Salih; Muhammad Ahmed (مجلة جامعة كركوك للعلوم الزراعية)
This experiment was carried out in Kirkuk governorate / Hawija district for the period from 2018 to 2019, using the design of the complete random sectors according to the split-split-split-split system with three replicates (Split-Split-Split Plot design in RCBD.), The first factor was the dates of the a cutting In which the forage crop was fed into the experiment, (the first on 18/12/2019, the second on 18/2/2019, the third on 4/5/2019, the fourth on 17/5/2019, the fifth on 1/7/2019), but The second factor was control treatments (without herbicide, herbicide), the third factor was seed rates (12, 24, 36 kg h-1), and the fourth factor was organic fertilizer (without fertilizer, 40, 80 tons h-1). The results showed that all of the insects were significantly superior when compared to the second group that recorded 50.69 gm-2 as the highest dry weight of broad-leaved weeds in this part of the experiment, and that the third and fourth germs were significantly superior to the rest of the insects by recording the largest wet weight of the feed and dry it reached 20227.6, 20098.1 Kg- h-1, respectively, for wet, and it was 2643.98 and 2756.24, respectively, for dry feed. It was found that spraying weed herbicides significantly affected reducing the weight of broad weeds to the minimum and by increasing the wet yield and reached 16764.3 kg h-1, in addition to that the same moral superiority occurred at the result of dry feed. With the mean of seed, the higher seed treatment significantly increased than the treatment of 12 kg.h-1 and 24 kg.h-1, which were 44.55 and 43.91 gm2, respectively, as the weight of the broad weed, and the wet weight yield increased progressively with the increase of the seed rate and the highest at the seed rate of 36 kg. h-1, and the highest yield of dry fodder when treated was 36 kg. h-1 2609.49 kg. h-1. The yield of wet fodder was significantly increased by adding 80 tons. h-1 of fertilizer, and it was 16,610.88 kg. h-1, and it was significantly higher by giving it the highest dry yield of 2563.71 kg. h-1. It is not possible to limit all the interference in this area of the research, but we are satisfied with mentioning only the summary of the main factors.